Pengaruh Struktur Modal, Ukuran Perusahaan, Pertumbuhan Perusahaan Dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Asuransi Yang Terdaftar DiBEI - Hidayah, Nur, Zulfa Irawati, S.E., M.Si (2015)
This study aimed to analyze the influence of positive and significant capital structure (DER), firm size (Size), Company Growth (Growth), and profitability (ROE) partially on Corporate Value (PBV) the insurance company listed on the Indonesia Stock Exchange period 2009-2013. The population in this study using insurance company listed on the Indonesia Stock Exchange 2009-2013 period. Samples are 6 insurance companies, where the sample method used was purposive sampling is a sampling method that takes an object with certain criteria. Data analysis method used is multiple linear regression analysis and hypothesis testing using t-statistic, the F-statistic and the coefficient of determination. From the analysis during the observation period t test results showed that the variable Capital Structure, Company Size and Growth Company partially no significant effect on company value, while Profitability positive and significant effect on the value of the Company. F test analysis results found that the variable capital structure (DER), firm size (Size), Company Growth (Growth) and profitability (ROE) jointly significant effect on the Company Value (PBV). Results of the analysis of the coefficient of determination (R ²) were obtained Adjusted R square (R ²) of 0,316, indicating that the company value can be explained by the variable Capital Structure, Company Size, Growth and Profitability Company is 31.6%, while the rest described 68, 4% are influenced by other factors beyond the variables studied. Keywords: Value Company, Capital Structure, Company Size, Company Growth